Analisis Enterprise Architecture pada PT. ABC - Ryan Andrianto Saputro; Leo Willyanto Santoso; Andy Setiabudi (Jurnal Infra, 2016)
PT. ABC is a trading – manufacturing company that works on hydraulic hose and hardware tools. PT. ABC’s marketing office and production site has a different location on a daily process. In business process, PT. ABC has information systems to support existing business processes. However, existing information systems does not commute the manufacturing line and only record their trading business. In addition, the existing information system is not perfect because there are still some recording is done manually.Based on the condition stated above, in this thesis, analysis and design of enterprise architecture information system is made for the company. The process begins with analyzing the business model and business strategy firm. Afterwards looking at the condition of information technology the enterprises has, the problems faced and the need of information technology in the future. Starting the design of data architecture, application architecture and technology architecture in accordance with the objectives, business strategy and business processes are made.The design of the data architecture for enterprise consists of several subsystems, namely Logistic Subsystem, Purchasing Subsystem, Marketing Subsystem, Accounting and Finance Subsystem, Human Resource Management Sub-System. A web-based application would be used for the new system ahead.